The Potential Of Judicial Review As An Incremental Business Strategy (The Emergence Of Sharing Economy And One-Stop Services Application In Indonesia) - Febrian Indar Surya Kusuma; Sapto Hermawan; Ardyllis Alves Soares (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
The digital economic system has changed the pattern of relationships between service providers and consumers in conducting transactions. Starting from the opportunity given by the Supreme Court to online taxi service providers as part of Micro, Small, and Medium Enterprises (from now on MSMEs), application services such as Go-Jek and Grab are now becoming new spaces for national economic growth. This study will specifically answer how the judicial review process becomes a form of incremental policy, which is very important for business continuity in the industrial era 4.0. This paper can fill the research gap regarding policy alternatives response in supporting the development of the digital economy in Indonesia. This paper will be portrayed using doctrinal research methods and statutory approaches in descriptive and prescriptive styles. As a result, this paper demonstrates that the Supreme Court, as the judiciary institution, plays a central role in responding to changing societal needs. The rationality of business actors in the theory of economic analysis of law has led them to step up and look for responsive policy alternatives. This condition is proven by the judicial review decision on Case Number 37 P/HUM/2017, which was then able to save MSME actors during the COVID-19 pandemic. The development of an incremental policy model is a form of government response to support national economic growth in the digital era, which demands rapid change.